(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Sars-Cov-19 virus has significantly challenged the Italian National Healthcare Service, which has been quickly adapting to the pandemic emergency in order to remain responsive and to optimize its functions. There are several lessons to be learned from the current CoViD-19 pandemic and this contribution offers some reflections and solutions for an effective public health emergency preparedness and response.